Pelayanan Publik Kereta Api di Yogyakarta Bagi Difabel - Wicaksono, Tio Tegar; Simamora, Jhon Ias Ganesa; Pradana, Glinggang Hima (INKLUSI, 2019)
The issue of discrimination against persons with disabilities in the field of public services, especially in transportation services, is still often heard. This research is focused on knowing the implementation of public services and how to optimize public services for persons with disabilities in Yogyakarta stations and Lempuyangan stations. This research is a normative-empirical study that combines the results of legal research with reality in the field. Field data was collected through observation and interview methods. The study found that accommodating the rights of persons with disabilities to public services at railway stations has several problems: lack of procedural mechanisms related to the implementation of human rights, institutions of persons with disabilities, and the existence of social-political factors of public policymakers who are not aware of the accommodation of human rights for disabled people. [Isu diskriminasi terhadap penyandang disabilitas di bidang pelayanan publik, khususnya dalam pelayanan jasa transportasi, masih sering terdengar. Penelitian ini difokuskan untuk mengetahui penyelenggaraan pelayanan publik dan cara mengoptimalkan pelayanan publik terhadap penyandang disabilitas di stasiun Yogyakarta dan stasiun Lempuyangan. Penelitian ini adalah penelitian normatif-empiris yang memadukan hasil-hasil penelitian hukum dengan kenyataan di lapangan. Data lapangan dikumpulkan dengan metode obersvasi dan wawancara. Penelitian ini menemukan bahwa: pengakomodasian hak penyandang disabilitas terhadap pelayanan publik di stasiun kereta api memiliki beberapa permasalahan: kurangnya mekanisme prosedural terkait pelaksanaan HAM, kelembagaan penyandang disabilitas, dan adanya faktor sosial politik pemangku kebijakan publik yang belum sadar akan pengakomodasian HAM bagi difabel.]